Sistem Pendukung Keputusan Teknik Trading Menggunakan Metode Simple Additive Weighting - Muhammad Luthfi Hakim; Winny Purbaratri; Nabilah Rahsa Pratiwi (Ikatan Ahli Informatika Indonesia, 2025)
This study aims to design and analyze a Decision Support System for cryptocurrency purchase decisions using the Simple Additive Weighting (SAW) method. This system was developed to assist investors in determining the best crypto assets based on technical indicators such as Fibonacci, Moving Average, and Stochastic. The research process included problem identification, data collection through interviews and observations, literature review, web-based system design using PHP and MySQL, and system testing. Each criterion was given a priority weight based on its influence on the decision, then a preference value was calculated for each cryptocurrency alternative: Bitcoin, Ethereum, Cardano, and Solana. The analysis results showed that Solana had the highest preference value (0.92), followed by Bitcoin (0.82), Cardano (0.68), and Ethereum (0.52), making Solana the best recommendation for purchase. The developed system is able to provide more objective, faster, and more efficient decision recommendations compared to manual analysis. Thus, the application of the SAW method has proven effective in supporting structured cryptocurrency investment decision-making based on technical indicators.